Evaluation Of Communal Wastewater Treatment Plant Operating Anaerobic Baffled Reactor And Biofilter - Evy Hendriarianti; Nieke Karnaningroem (Waste Technology, 2016)
Construction of communal Waste Water Treatment Plant, WWTP in city of Malang since 1998 but until recently had never done an evaluation the performance. Communal WWTP performance evaluation is needed to see how far the efficiency of processing result. Until now, Environmental Agency Malang City only measure effluent from WWTP Communal  to know the suitability  with domestic wastewater quality standards. Effluent quality data in 2014 showed value above the quality standard of domestic wastewater from East Java Governor Regulation No. 72 in 2013 for parameters BOD and COD. WWTP Communal USRI research objects are on a six (6) locations by involving the user community during the planning, construction, operation and maintenance. Technology choice of ABR followed by a biofilter reactor with the stone media proved capable of processing organic matter of BOD and COD with the removal levels respectively by 78% -99% and 71% -99%. As for the parameters of TSS, NO3 and PO4 have the ranges of removal respectively by 56% -100%, (43%) - 72%, (2%) - 13%. Ratio BOD and COD in influent are low and ranged from 0.22 to 0.41. From the evaluation shows that high organic matter concentrations in influent along with the HRT and operation time high will result in a higher removal level